2011
DOI: 10.1128/mcb.06120-11
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Lactate Dehydrogenase A Is Important for NADH/NAD+ Redox Homeostasis in Cancer Cells

Abstract: The Warburg effect describes an increase in aerobic glycolysis and enhanced lactate production in cancer cells. Lactate dehydrogenase A (LDH-A) regulates the last step of glycolysis that generates lactate and permits the regeneration of NAD ؉ . LDH-A gene expression is believed to be upregulated by both HIF and Myc in cancer cells to achieve increased lactate production. However, how oncogenic signals activate LDH-A to regulate cancer cell metabolism remains unclear. We found that the oncogenic receptor tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
186
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(199 citation statements)
references
References 30 publications
10
186
2
1
Order By: Relevance
“…Their expression levels were not measured separately, but LDHA is presumably responsible for the increased expression observed in our adenomas. LDHB expression is in most cases epigenetically silenced in colon cancer cells (44,45), whereas LDHA is overexpressed, and its activity is maintained via the oncogenic tyrosine kinase FGFR1 (46). LDHA is a key player in the reversible conversion of pyruvate to lactate during aerobic glycolysis, a typical feature of cancer cell metabolism first described by Warburg (47).…”
Section: Discussionmentioning
confidence: 99%
“…Their expression levels were not measured separately, but LDHA is presumably responsible for the increased expression observed in our adenomas. LDHB expression is in most cases epigenetically silenced in colon cancer cells (44,45), whereas LDHA is overexpressed, and its activity is maintained via the oncogenic tyrosine kinase FGFR1 (46). LDHA is a key player in the reversible conversion of pyruvate to lactate during aerobic glycolysis, a typical feature of cancer cell metabolism first described by Warburg (47).…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations were introduced using QuikChange-XL sitedirected mutagenesis kit (Stratagene). [5-3 H]glucose and [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]pyruvate were purchased from PerkinElmer, and R-[ 3 H]lipoic acid was purchased from American Radiolabeled Chemicals. Stable knockdown of endogenous PDP1 was achieved using a lentiviral vector harboring an shRNA construct (Open Biosystems; 5Ј-GTTCAGTTCAATTCTCAT-GTT-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…293T, MDA-MB231, MCF7, human foreskin fibroblast, and HaCaT cells were cultured in Dulbecco's modified Eagle's medium (DMEM) with 10% FBS. TKI258 (generously provided by Novartis Pharma) treatment was performed by incubating cells with 1 M TKI258 for 4 h. For the cell proliferation assay, 125 nM oligomycin was added in the cell culture medium as described previously (13). Imatinib was purchased from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
“…LDHA is an enzyme that converts pyruvate into lactate, and some studies suggested that phosphorylation of LDHA increases its activity and induces the Warburg effect (49,50), although this does not appear to be the case in Sirt6-deficient retina. VHL regulates protein degradation and downregulates HIF2A, which is reflected in our data by the decreased levels of VHL and the increased levels of HIF2A.…”
Section: Pde6bmentioning
confidence: 99%